The Quality of Maternity Services in Mashhad Educational Hospitals, Using SERVUSE Model - Fariba Askari; Nahid Maleki-Saghooni; Eisa Nazar; Zahra Hadizadeh Talasaz; Ali Vafaee Najar (Journal of Health Management & Informatics, 2018)
Introduction: Reducing maternal and neonatal mortality requires improved care quality; the aim of this study was to determine various dimensions of the quality of services in maternity wards in Iran from the patient’s perspective. Methods: In this cross-sectional study which was conducted from April to October 2017, 363 patients were selected from maternity wards of five hospitals affiliated to Mashhad University of Medical Sciences by convenience sampling method. Data collection tools consisted of the SERVUSE (Service Usability questionnaire), including 51 items in 6 dimensions of services quality; its validity and reliability were determined in previous studies. Data analysis was performed using SPSS, version 20. The analysis was performed using descriptive and inferential statistical methods including Wilcoxon, Kruskal Wallis and Mann-Whitney tests. The significance level in all the tests was considered 5%. Results: The total mean scores of the patients’ expectation and perception were 19.10±2.14 and 15.11±4.25, respectively. The highest expectation and perception were related to the usability dimension, and the lowest expectation and perception were related to reliability dimension. The differences between the median score of perception and expectation for all dimensions and total median score of perceptions and expectations were statistically significant (P<0.05, using Wilcoxon test). There were no statistically significant differences in the median score of the gap between the patient’s expectations and perceptions at the levels of demographic variables (P>0.05, using Mann-Whitney and Kruskal Wallis tests). Conclusion: It seems that the service quality of maternity ward of hospitals was approximately unsatisfactory from the patients’ perspective, and they had high expectations in maternity wards of hospitals. Since maternity service quality is critically important, improvement of quality requires management, concordant participation, and efforts of the hospital and staff at all levels of the medical facilities and convenience.